Density functional theory calculation on CN adsorption on pyrite (100) surface-doped As impurity. (November 2015) - Chen, M. L.; Chen, J. H.; Li, Y. Q.; Deng, J. H.
Abstract : The influence of arsenic (As) on CN molecule adsorption on the pyrite FeS2 (100) surface was researched by density functional theory calculations. CN adsorption is enhanced by the presence of As impurity. Mulliken bond and charge population results show that the degree of covalency of bonded C–Fe is enhanced in the introduction of As impurity. The density of states of the atoms in reaction shows that it is mainly the Fe d state that loses electrons and transfers to the empty p states of C and N atoms, forming d→p back bonding on both perfect and As-bearing surfaces. In addition, on the As-bearing surface, the Fe d state obtains electrons from As 4p state, resulting in the accumulation of electrons on Fe sites and conducive to the adsorption of CN.